The big five model in bipolar disorder: a latent profile analysis and its impact on longterm illness severity - Niklas Ortelbach; Jonas Rote; Alice Mai Ly Dingelstadt; Anna Stolzenburg; Cornelia Koenig; Grace O’Malley; Esther Quinlivan; Jana Fiebig; Steffi Pfeiffer; Barbara König; Christian Simhandl; Michael Bauer; et al. (International Journal of Bipolar Disorders, 2022)
Abstract Background Using a personality typing approach, we investigated the relationship between personality profiles and the prediction of longterm illness severity in patients with bipolar disorder (BD). While previous research suggests associations between BD and traits from the NEO-FFI profiles, the current study firstly aimed to identify latent classes of NEO-FFI profiles, and, secondly, to examine their impact on the longterm prognosis of BD. Methods Based on the NEO-FFI profiles of 134 euthymic patients diagnosed with BD (64.2% female, mean age = 44.3 years), successive latent profile analyses were conducted. Subsequently, a subsample (n = 80) was examined prospectively by performing multiple regression analysis of the latent classes to evaluate the longitudinal course of the disease (mean: 54.7 weeks) measured using a modified Morbidity Index. Results The latent profile analyses suggested a 3-class model typifying in a resilient (n = 68, 51%), vulnerable (n = 55, 41%) and highly vulnerable (n = 11, 8%) class. In the regression analysis, higher vulnerability predicted a higher longterm Morbidity Index (R 2 = 0.28). Conclusions Subgroups of patients with BD share a number of discrete personality features and their illness is characterized by a similar clinical course. This knowledge is valuable in a variety of clinical contexts including early detection, intervention planning and treatment process.